2022-RA-703-ESGO Primary and interval debulking surgery in advanced ovarian cancer: real-world clinical outcomes of patients in 1st line setting, analysis from the french national ESME-unicancer database. (20th October 2022) - Costaz, Hélène; Boussere, Amal; Thomas, Quentin Dominique; Ray-Coquard, Isabelle; Pomel, Christophe; Gladieff, Laurence; Marchal, Frédéric Marchal; Laas, Enora; Rouzier, Roman; Sabatier, Renaud; Floquet, Anne; Rouge, Thibault de la Motte; et al.
Abstract : Introduction/Background: Primary cytoreductive surgery is the standard of care for advanced ovarian cancer. This work would like to explore the prognostic according the surgical management in advanced ovarian cancer of a real-world multicentre cohort. Methodology: A non-interventional, retrospective study in patients selected from the Epidemio-Strategy and Medical Economics (ESME) Ovarian Cancer (OC) Data Platform of Unicancer, a multicentre real-life database using a supervised, retrospective data collection process was conducted. Patients treated with surgery for advanced ovarian cancer between January 01, 2011 and December 31, 2017 in 18 French Comprehensive Cancer Centers (FCCC) were included. The database was locked on January 01, 2020. Propensity scores were performed in population analyses. Results: 1831 female patients with FIGO stage III or IV ovarian cancer at diagnosis underwent surgery, including 879 (48%) primary debulking surgery (PDS) and 952 (52%) interval debulking surgery (IDS). The median follow-up was 59.2 months CI 95% [57.1–61.7]. The median overall survival (OS) was 90.4 months for PDS, CI95% [79.4–95.3] and 47.8 months for IDS, CI95% [43.3–54.1], HR = 0.48 CI 95% [0.41–0.56], p<0.0001. The median progression-free survival (PFS) was 23.6 months for PDS, CI95% [20.9–26.1] and 14.3 months for IDS, CI95% [13.0–16.0], HR = 0.66 CI95% [0.59–0.75], p<0.0001. In the multivariate Cox analysis, the covariates treatment strategy (PDS versus IDS) HR = 0.57 CI 95% [0.44–0.74], p<0.0001, and residual tumor after surgery HR = 1.78 CI 95% [1.25–2.53], p<0.0001 remain significant as a PFS prognostic factors. The OS prognostic factors was the covariates treatment strategy (PDS versus IDS) (p<0.002), residual tumor after surgery (p<0.0001), age at diagnosis (p<0.02) and BRCA mutation (p<0.02). Conclusion: Our data of real-world are in line with those reported in clinical trial for patient with advanced ovarian cancer in 1sr line setting with surgical treatment.